THE VITAL SIGNIFICANCE OF FORMING PROFESSIONAL SPIRITUALITY AND IMMOBILIZING THEM INTO STUDENTS' CONSCIOUSNESS THROUGH EDUCATIONAL LESSONS (Intent Research Scientific Journal, 2023)
The article deals with some recommendations for the development of professional spirituality of students by studying foreign experiences, as well as the great legacy of our great ancestors.